Coherent Photoproduction of Proton-Antiproton Pairs on Deuterium - Y. S. Ghandilyan
Photoproduction of hadron-antihadron pairs on deuterium with 4.5÷5.5 GeV energy bremsstrahlung photon beam is presented. Coherent production of π+π−, Κ+Κ−, pp pairs has been studied in fully exclusive final state. The goal of this analysis is to study t-channel production of hadron pairs in the mass range > 2 GeV, simultaneously this is a good opportunity to study claims for pp resonances. Coherent production on nuclei often used to suppress s- and u-channel production processes in meson spectroscopy studies. The data presented here have been obtained at the (TJNAF) Thomas Jefferson National Accelerator Facility, USA, using the Continues Electron Beam Accelerator Facility (CEBAF) Large Acceptance Spectrometer and the bremsstrahlung tagged photon facility in experimental Hall-B.
Keywords: Physics; Physics of elementary particles